What was Mughal cuisine?: Defining and analysing a culinary culture - Narayanan, Divya (Interdisziplinäre Zeitschrift für Südasienforschung, 2016)
This article aims at interrogating the problem of defining and analysing a culinary culture, with special reference to what may loosely be termed as ‘Mughal cuisine’. The essay begins with a discussion of the issues inherent to defining the boundaries of ‘Mughal cuisine’ in terms of what constitutes ‘Mughal’ and what may be classified as a ‘cuisine’. This is followed by a discussion of various anthropological approaches to analysing cuisine, with particular emphasis on structuralism and its critiques. The article then goes on to draw on works by Elisabeth Rozin and Richard Dawkins to formulate a ‘flavour meme’ concept as an alternative analytical paradigm. However, it is emphasised that this is not necessarily intended as a universal model to be applied without regard to historical and cultural context. The conclusion advocates that cuisine, as a phenomenon, be analysed as a transcultural process rather than as a structure.